What is the effective clinical use of small bowel capsule endoscopy in real life? - Akyüz, Filiz; Çavuş, Bilger; Akyüz, Ümit (Turkish Journal of Gastroenterology, 2020)
Capsule endoscopy is a noninvasive and easy method for evaluating the gastrointestinal tract. Since the wireless capsule endoscopy system was first developed, many new technical improvements have been made in order to gain maximum benefit from the procedure. However, at this stage, it remains a diagnostic modality, the main indication for its use being obscure gastrointestinal bleeding. Capsule endoscopy is only contraindicated in symptomatic intestinal obstruction. New indications for use and therapeutic options may become possible with the further development of nanotechnologies.